DURAL AVF CAUSING A TREATABLE CJD LIKE COGNITIVE DYSFUNCTION. Issue 11 (14th October 2015) - Randall, Anna; Ellis, Richard James Booth; Hywel, Brython; McCoy, Christopher Andrew; Davies, Rhys; Eldridge, Paul Richard; Putharan, Mani; Radon, Mark; Alusi, Sundus
Abstract : A 67-year-old woman presented with a seven-month history of progressive psychiatric disturbance and sub-acute cognitive decline mimicking Creuztfeldt-Jakob Disease. She presented initially to Psychiatry with worsening anxiety, depression, lassitude, impaired concentration and insomnia. She was given a diagnosis of agitated depression. She subsequently experienced episodes of disorientation, indecision and inability to complete routine, learned tasks as well as visual hallucinations. Initial investigations for causes of subacute dementia were unremarkable including a non-diagnostic MRI. However, five months into her presentation, there was further rapid deterioration with fluctuating consciousness and deteriorating mobility. She became bedbound, incontinent and cortically blind. She had right hemiparesis, hemineglect, extrapyramidal features, and extensor plantars. A 4D computerised tomography angiogram demonstrated a dural arteriovenous (AV) fistula with retrograde filling of superior sagittal sinus and cortical venous congestion. She underwent emergency Onyx embolisation. Over a few weeks, there was gradual improvement in her anxiety, cognition and mobility. She had a mild residual right hemiparesis. Intracranial dural AV fistulae can present with a spectrum of neurological symptoms, including cognitive decline. A lowhigh index of suspicion combined with close liaison between Neuroradiology, Neurology and Neurosurgery ensures prompt diagnosis and maximises the potential for cognitive recovery.